2020
DOI: 10.1093/europace/euaa004
|View full text |Cite
|
Sign up to set email alerts
|

A collective European experience with left atrial appendage suture ligation using the LARIAT+ device

Abstract: Aims We report the collective European experience of percutaneous left atrial appendage (LAA) suture ligation using the recent generation LARIAT+ suture delivery device. Methods and results A total of 141 patients with non-valvular atrial fibrillation and contraindication to oral anticoagulation (OAC), thrombo-embolic events despite OAC or electrical LAA isolation were enrolled at seven European hospitals to undergo LAA ligat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…Improved features compared to the first generation of the device include snare expansion from 40 to 45 mm, improved catheter torque‐ability, and orientation under fluoroscopy. Initial European experience with the device by Tilz et al demonstrated a 97.1% success in LAA closure (<5 mm residual leak) after a mean follow up of 6 months, with acceptably low (2.8%) access complications and peri‐procedural serious adverse events 33 . Larger prospective studies with longer follow up periods are warranted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Improved features compared to the first generation of the device include snare expansion from 40 to 45 mm, improved catheter torque‐ability, and orientation under fluoroscopy. Initial European experience with the device by Tilz et al demonstrated a 97.1% success in LAA closure (<5 mm residual leak) after a mean follow up of 6 months, with acceptably low (2.8%) access complications and peri‐procedural serious adverse events 33 . Larger prospective studies with longer follow up periods are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…32 Improved features compared to the first generation of the device include and peri-procedural serious adverse events. 33 Larger prospective studies with longer follow up periods are warranted. Insights from the LAFIT-LARIAT registry show that LAA exclusion improves mechanical function of the left atrium resulting in reverse left atrial remodeling.…”
Section: The Second Generation Lariat+ Device and Future Prospectsmentioning
confidence: 99%
“…The second-generation LARIAT + has improved features, such as snare expansion from 40 mm to 45 mm, the addition of a platinum–iridium ‘L’ Marker that allows identification of the device orientation under fluoroscopy, and a stainless steel wire braid on catheter shaft that provides improved ‘torque-ability’ of the catheter. Initial reports from registries highlight the high rates of acute and short-term LAAC, paired with low periprocedural complications and few thromboembolic events at longer term follow-up [ 205 , 206 ].…”
Section: Left Atrial Appendage Closurementioning
confidence: 99%
“…The benefit of using colchicine has also been demonstrated by Gunda et al [30]. Additional data on complication rates have been reported by other groups [31][32][33]. As part of a systematic review by Chaterjee et al published in 2015, the authors included a specific analysis of adverse events from real-world practice using the FDA MAUDE database [31].…”
Section: Endo-epicardial Closure To Achieve Laaei -The Lariat Devicementioning
confidence: 99%
“…As part of a systematic review by Chaterjee et al published in 2015, the authors included a specific analysis of adverse events from real-world practice using the FDA MAUDE database [31]. Very recently, Tilz et al reported on the collective European experience [32]. In their series of 141 patients, successful deployment of the Lariat device was achieved in 97.8%.…”
Section: Endo-epicardial Closure To Achieve Laaei -The Lariat Devicementioning
confidence: 99%